Accuracy of digital and film panoramic radiograph for assessment the sites of periapical bone lesions (comparative study ) (Mustansiria Dental Journal, 2018)
The dental pulp is a delicate connective tissue , it react to bacterial infection or toother stimuli by an inflammatory response .Once infection has been established in thepulp , spread of the process can be through the root canals and into the periapicallesions.The aim of this study was to evaluate the accuracy of digital and film panoramicradiographs in detection the periapical bone lesion in different sites ,which detectedpreviously by periapical radiographs .In this study 106 teeth were examined by intraoral periapical radiographs which indicated that only 60 teeth were with periapicalbone lesion , then by both digital and film panoramic the teeth with periapical lesionwere examined .The results show significant advantage of digital panoramic whichshow the same mean of periapical lesion like conventional periapical radiographs ,also the study show significant differences between digital and film panoramicradiographs in incisor region for the detection of periapical bone lesion .